Multiple Plant Growth–Promoting Activities Exhibited by Root-Associated Bacteria Isolated From Bamboo and Corn - Camille Andrea R. Flores; Maria Auxilia T. Siringan; Mary Ann Cielo V. Relucio-San Diego (International Journal of Microbiology)
Plant growth–promoting bacteria found in the plant roots and rhizosphere stimulate growth and reduce plant diseases through various direct and indirect mechanisms. They are proven as efficient biofertilizers that enable farmers to reduce or eliminate the use of expensive and environmentally harmful chemical fertilizers. The goal of this study was to isolate, characterize, and identify nitrogen-fixing bacteria with additional plant growth–promoting traits from the roots of bamboo (Bambusa sp.) and corn (Zea mays L.) grown in Cagayan Province, Philippines. A total of 27 bacteria were isolated and identified based on 16S rRNA gene sequencing and phylogenetic analysis. Selected isolates were also subjected to whole-genome sequencing to obtain accurate identification. The isolates were classified into 12 genera, the majority of which belonged to Leclercia, Pantoea, Klebsiella, and Exiguobacterium. Assays for four plant growth–promoting activities revealed that all isolates exhibited at least two activities in vitro. Four isolates (15%) tested positive for the nitrogen-fixation gene nifH, which was mostly detected in Klebsiella isolates. Eleven (41%) solubilized phosphate and Pantoea isolates showed the highest potential. All strains (100%) synthesized indole-3-acetic acid (IAA), and 24 (89%) produced siderophores. Notably, Enterobacter roggenkampii strain B1-01 and Klebsiella oxytoca strain B1-04 displayed all the examined plant growth–promoting traits. Our findings demonstrated that the roots of bamboo and corn host a variety of beneficial bacteria exhibiting significant plant growth–promoting activities under in vitro conditions. These strains could be used for future investigations into microbe–plant interactions and have the potential to be harnessed for various agricultural applications.